(untitled) (Research, Society and Development, 2022)
Sorghum (Sorghum bicolor L., Poaceae) plays an essential role in subsistence agriculture and in the food of millions of people, it is considered a crop of great importance in the world. The study aimed to monitor the development of sorghum (Sorghum bicolor) grown in pots with the addition of goat manure. The experiment was carried out at the State University of Alagoas (UNEAL) from August 2021 to November 2021. Sorghum (Sorghum bicolor) seeds were sown in a seedbed with carbonized rice husk substrate, and after germination, were transplanted to the pots, where they had the mixture of soil plus goat manure in different doses. The experimental arrangement was in DIC, with twenty pots, separated into four treatments and five replications. Treatment 1 (T1), treatment 2 (T2), treatment 3 (T3) and treatment 4 (T4). All data analyzed in the experiment were recorded in an Excel spreadsheet. The results obtained through the tukey test at 5%, showed that the experiments with higher doses of manure, presented greater phenological development.